Avaliação do conhecimento de enfermeiros da rede de atenção à saúde no município de Bauru (SP) sobre cuidado aos pacientes com feridas: um estudo transversal - Hoelz, Cassia Marques da Rocha [UNESP] (2015)
Introduction: Ulcers or wounds are a serious problem for public health and nursing care. There are few studies assessing the knowledge that nurses have about wound care. Objectives: To identify the knowledge of wounds that nurses from the public health care system have. Method: It is a cross-sectional, descriptive and analytical study, with 166 nurses who work in public health assistance institutions in Bauru and answered a structured questionnaire from May to September 2014. The questionnaire was developed by two experts, and the answers were considered appropriate according to / in accordance with systematic reviews and guidelines. Categorical variables were represented by percentage fractions and compared among subgroups using the chi-square test. The subgroups were compared using generalized linear models. As a final product, it was proposed and developed a thematic short course in a virtual environment for training in wounds care. Results: There was a predominance of females (88%), average age of 37.2 years; 10.7 years after graduation; 9.9 years of professional activity. Most of them graduated from private educational institutions. The predominant workplace was the hospital network (41.6%) and 85.5% of the participants perform care functions. The knowledge acquired during graduation was considered from regular to good by 82%, and 64.5% mentioned some kind of update on wounds. In addition, 86.3% of nurses said that they assist patients with wounds; 62.7% declared that there are dressing protocols in their institutions; 65.1% answered that the nurse performs a nurse consultation and prescribes a standardized dressing; and 91.6% informed that the dressing is performed by an auxiliary or nursing technician. According to 74.7% of the participants, the health professional performs the dressing following the nurse prescription. Among the therapeutic methods, the collagenase ointment is the most known (96.4%) and used (78.9%). The Unna ...